Synthesis, Structural Characterization and Photodecarbonylation Study of a Dicarbonyl Ruthenium(II)‐Bisquinoline Complex. Issue 5 (22nd May 2019) - Kubeil, Manja; Joshi, Tanmaya; Wood, Bayden R.; Stephan, Holger
Abstract: A photoactivatable ruthenium(II) carbonyl complex mer, cis ‐[Ru(II)Cl(BisQ)(CO)2 ]PF6 2 was prepared using a tridentate bisquinoline ligand (BisQ=(2, 6‐diquinolin‐2‐yl)pyridin). Compound 2 was thoroughly characterized by standard analytical methods and single crystal X‐ray diffraction. The crystal structure of the complex cation reveals a distorted octahedral geometry. The decarbonylation upon exposure to 350 and 420 nm light was monitored by UV/VIS absorbance and Fourier transform infrared spectroscopies in acetonitrile and 1 % (v/v) DMSO in water, respectively. The kinetic of the photodecarbonylation has been elucidated by multivariate curve resolution alternating least‐squares analysis. The stepwise decarbonylation follows a serial mechanism. The first decarbonylation occurs very quickly whereas the second decarbonylation step proceeds more slowly. Moreover, the second rate constant is lower in 1 % (v/v) DMSO in water than in acetonitrile. In comparison to 350 nm irradiation, exposure to 420 nm light in acetonitrile results in a lower second rate constant. Abstract : Time to release : A ruthenium(II) complex based on tridentate bisquinoline ligand exhibits suitable electronic and decarbonylation properties upon irradiation using UV light. Attachment of additional groups to this π‐electron rich complex structure gives the possibility to shift the absorption range into the visible spectrum, and to couple biomolecules for targeting.